2019
DOI: 10.1557/mrc.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Programmable microscale stiffness pattern of flat polymeric substrates by temperature-memory technology

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The fixation ratios are investigated to be higher than 100% for the medium depth and large depth programing at lower temperatures on compressed microcuboids. A similar observation has been reported for compression programing of the cPEVA microstructured surface, and this may be introduced by crystallization-induced contraction during fixation under higher stress, which is more obvious for the compressed microcuboids that have higher orientation in the crystalline structures …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The fixation ratios are investigated to be higher than 100% for the medium depth and large depth programing at lower temperatures on compressed microcuboids. A similar observation has been reported for compression programing of the cPEVA microstructured surface, and this may be introduced by crystallization-induced contraction during fixation under higher stress, which is more obvious for the compressed microcuboids that have higher orientation in the crystalline structures …”
Section: Resultssupporting
confidence: 77%
“…A similar observation has been reported for compression programing of the cPEVA microstructured surface, and this may be introduced by crystallization-induced contraction during fixation under higher stress, which is more obvious for the compressed microcuboids that have higher orientation in the crystalline structures. 26 The shape recovery of the nanocavities induced by step-wise online heating was observed using AFM, and their height images are shown in Figure S2. It can be observed that all the programed cavities turn back to a smooth surface during heating, and the recovery route varies among different samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%